ChemInform Abstract: Crystal Structure and High‐Temperature Phase‐Transitions in SrNdMRuO6 (M: Zn, Co, Mg, Ni) New Double Perovskites Studied by Symmetry‐Mode Analysis. Issue 16 (28th March 2013) - Iturbe‐Zabalo, E.; Igartua, J. M.; Faik, A.; Larranaga, A.; Hoelzel, M.; Cuello, G. J.
Abstract The room temperature structures and temperature induced structural phase transitions of the title compounds are determined by X‐ray, synchrotron radiation, and neutron powder diffraction.